2021
DOI: 10.1136/bmjopen-2021-054365
|View full text |Cite
|
Sign up to set email alerts
|

POSNOC—POsitive Sentinel NOde: adjuvant therapy alone versus adjuvant therapy plus Clearance or axillary radiotherapy: a randomised controlled trial of axillary treatment in women with early-stage breast cancer who have metastases in one or two sentinel nodes

Abstract: IntroductionACOSOG-Z0011(Z11) trial showed that axillary node clearance (ANC) may be omitted in women with ≤2 positive nodes undergoing breast conserving surgery (BCS) and whole breast radiotherapy (RT). A confirmatory study is needed to clarify the role of axillary treatment in women with ≤2 macrometastases undergoing BCS and groups that were not included in Z11 for example, mastectomy and those with microscopic extranodal invasion. The primary objective of POsitive Sentinel NOde: adjuvant therapy alone versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 12 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Currently, patients undergoing mastectomy are still being enrolled in the study to increase its power. In the POSNOC trial 34 , 1900 patients with cT1–2 N0 breast cancer and 1 or 2 macrometastatic SLNs are being randomized between adjuvant systemic therapy and adjuvant systemic therapy with either ALND or axillary RT, with 5-year axillary recurrence rate as the primary endpoint. The first results are expected in 2026.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, patients undergoing mastectomy are still being enrolled in the study to increase its power. In the POSNOC trial 34 , 1900 patients with cT1–2 N0 breast cancer and 1 or 2 macrometastatic SLNs are being randomized between adjuvant systemic therapy and adjuvant systemic therapy with either ALND or axillary RT, with 5-year axillary recurrence rate as the primary endpoint. The first results are expected in 2026.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint is axillary recurrence at 5 years. As of June 2021, POSNOC study had completed 1866 cases [ 25 ]. The results of the ACOSOG Z0011 and IBCSG 23-01 studies have changed the previous breast cancer treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…PhH3 is a proliferation marker that is specific for mitosis, as it is expressed from the late G 2 phase to M transition, and rapidly degrades on entry into the G 1 phase [37]. Therefore, PhH3 labelling has been reported to closely correlate with mitotic figure detection on standard haematoxylin and eosin (H&E)stained sections [38,39]. As compared with the MAI, PhH3 is relatively easy to assess, as its bright staining offers easy visualisation of mitotic figures by morphology, resulting in a high accuracy of detection.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, small metastatic deposits such as micro-metastases and isolated tumor cells were observed more frequently [35][36][37]. Then, the Z0011 and AMAROS trials revealed that completion ALND (cALND) may be omitted in clinically node negative patients with one or two metastatic sentinel lymph nodes (SLNs) [38,39], and as a consequence information about the overall number of involved lymph nodes is no longer routine practice. This loss of detail on the extent of nodal involvement does not compromise outcome [38,39], but may affect the clinical decision-making process and certainly comes with a sense of uncertainty for many clinicians.…”
Section: Towards Better Selection Of Patients In Need Of Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation